2006
DOI: 10.1016/j.palaeo.2006.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Controls on carbonate and terrigenous deposition in the incipient Benguela upwelling system during the middle to the late Miocene (ODP Sites 1085 and 1087)

Abstract: This study deals with the variability of biogenic carbonate and terrigenous depositional patterns in the Cape Basin area of the South Atlantic during the middle to the late Miocene focusing on ODP Sites 1085 and 1087 sediments at the Benguela Upwelling area, Southwest Africa. The investigations are based on grain-size analysis and clay mineralogy. The sedimentary records at both sites provide information about climate and environmental changes. The direct input of terrigenous material from southwestern Africa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 45 publications
4
15
0
1
Order By: Relevance
“…6c). This rise is consistent with the findings of Kastanja et al (2006), who also found an enhanced MAR TOC from 11.8 Myr on. It also coincides in time with the rise of MAR bulk .…”
Section: Organic Sedimentationsupporting
confidence: 92%
See 4 more Smart Citations
“…6c). This rise is consistent with the findings of Kastanja et al (2006), who also found an enhanced MAR TOC from 11.8 Myr on. It also coincides in time with the rise of MAR bulk .…”
Section: Organic Sedimentationsupporting
confidence: 92%
“…This study incorporates and expands the results and findings of earlier studies by Kastanja et al (2006) who showed, that dust input from the Namib desert started to become identificable after 11.2 Myr. This gives indications for the establishment of a major shift in the wind regime, which has been a main precondition for the development of the wind-driven Benguela Upwelling System (BUS).…”
Section: Introductionsupporting
confidence: 79%
See 3 more Smart Citations